HUBUNGAN PENGETAHUAN DAN PERILAKU DALAM MEMPEROLEH ANTIBIOTIK SECARA PER ORAL DI BEBERAPA APOTEK DI SURABAYA - I Wayan L.D. Purnamahardika; Anita Purnamayanti (Perpustakaan Universitas Surabaya, 2018)
Abstract – According to Yusuf Sholihan (2015) in Surakarta city as much as 64,86% of respondents had bought antibiotics without prescriptions respondents with poor knowledge of antibiotics were 36,96%. Antibiotic resistance is currently the greatest threat to global public health. This study aimed to analyze the correlation between knowledge and behavior of the respondents in seeking antibiotics at several pharmacies Surabaya. This was a cross sectional research using questionnaire to analyze respondents knowledge of antibiotics and checklistto analyze antibiotics seeking behavior. The results of this study indicated most of the respondents were at good level of knowledge ( 42.31%); while respondents with poor level of knowledge were 21.15%. All the respondents received the prescribed antibiotics, indicating that the antibiotic seeking behavior were correct, the correlation analysis between level of knowledge and antibiotics seeking behaviour using spss could not be performed, because there was no variation in behavior. Based on the percentage of the highest level of knowledge, it had been concluded that there was correlation between the level of knowledge with antibiotics seeking behavior.